Rare Extra‐Axial Chordoma of the Anteromedial Thigh: A Case Report - Meagan E. Tibbo; Nishad Mysore; Jean Jose; Andrew E. Rosenberg; H. Thomas Temple (2025)
ABSTRACT Chordomas are rare notochordal malignancies typically occurring in the axial skeleton. Less than 100 extra‐axial chordomas have been reported. We describe a unique chordoma of the anteromedial thigh. The clinical presentation of extra‐axial chordomas is highly variable; thus, recognizing this entity in the differential diagnoses of extra‐axial bone/soft tissue tumors is important.